Prognostic value of left ventricular remodelling index in idiopathic dilated cardiomyopathy. (13th July 2020) - Xu, Yuanwei; Lin, Jiayi; Liang, Yaodan; Wan, Ke; Li, Weihao; Wang, Jie; Zhu, Yanjie; Mui, David; Wang, Lili; Li, Yuancheng; Cheng, Wei; Sun, Jiayu; et al.
Abstract: Aims: To evaluate the prognostic value of left ventricular (LV) remodelling index (RI) in idiopathic dilated cardiomyopathy (DCM) patients. Methods and results: We prospectively enrolled 412 idiopathic DCM patients and 130 age- and sex-matched healthy volunteers who underwent cardiovascular magnetic resonance imaging between September 2013 and March 2018. RI was defined as the cubic root of the LV end-diastolic volume divided by the mean LV wall thickness on basal short-axis slice. The primary endpoint included all-cause mortality and heart transplantation. The secondary endpoint included the primary endpoint and heart failure (HF) readmission. During the median follow-up of 28.1 months (interquartile range: 19.3–43.0 months), 62 (15.0%) and 143 (34.7%) patients reached the primary and secondary endpoints, respectively. Stepwise multivariate Cox regression showed that RI [hazard ratio (HR) 1.20, 95% confidence interval (CI) 1.11–1.30, P  <   0.001], late gadolinium enhancement (LGE) presence and log (N-terminal pro-B-type natriuretic peptide) were independent predictors of the primary endpoint, while RI (HR 1.15, 95% CI 1.08–1.23, P  < 0.001) and extracellular volume were independent predictors of the secondary endpoint. The addition of RI to LV ejection fraction (EF) and LGE presence showed significantly improved global χ 2 for predicting primary and secondary endpoints (both P  < 0.001). Furthermore, RI derived from echocardiography also showed independent prognostic value for primary and secondary endpoints with clinical risk factors. Conclusions: RI is an independent predictor of all-cause mortality, heart transplantation, and HF readmission in DCM patients and provides incremental prognostic value to LVEF and LGE presence.